Lowland Grazing And Marburg Virus Disease (MVD) Outbreak In Kween District, Eastern Uganda - Siya, Aggrey; Bazeyo, William; Tuhebwe, Doreen; Tumwine, Gabriel; Ezama, Arnold; Manirakiza, Leonard; Kugonza, Donald R.; Rwego, Innocent B. (BMC Public Health, 2019)
Uganda is one of the few countries in Africa that has been experiencing outbreaks of viral hemorrhagic fevers such as Ebola, Marburg and Crimean-Congo Hemorrhagic fevers. In 2017 Uganda experienced a Marburg Virus Disease (MVD) outbreak with case fatality rate of 100% in Kween district. Although hunting for wild meat was linked to the MVD outbreak in Kween district, less was reported on the land use changes, especially the changing animal grazing practices in Kween district.Through Makerere University One Health graduate fellowship program with attachment to Uganda Red Cross Society, a study was conducted among the agricultural communities to elucidate the risk behaviors in Kween district that can be linked to the 2017 Marburg disease outbreak.Results show that although a few elderly participants ascribed fatal causes (disobedience to gods, ancestors, and evil spirits) to the MVD outbreak during FGDs, majority of participants linked MVD to settling in caves (inhabited by Fruit Bats) during wet season as upper belts are extensively used for crop production leaving little space for animal grazing. Members also noted side activities like hunting for wild meat during this grazing period that could have predisposed them to Marburg Virus.There is need to integrate One Health concepts within agricultural extension service provision in Uganda so as to enhance the management of such infectious diseases.
Keywords: Agriculture, Livelihoods, Zoonotic diseases, One health